Numerical prediction of deformation in thin-plate welded joints using equivalent thermal strain method. (December 2020) - Wu, Chunbiao; Kim, Jae-Woong
Abstract: Large welding-induced distortions are inevitably generated in a thin-plate welded joint due to its weak stiffness. In this study, an equivalent thermal strain method based on inherent strain theory is proposed to predict the welding deformation of thin plates. An artificial temperature and an orthotropic thermal expansion coefficient are adopted to directly simulate the welding shrinkage and bending behavior of the cooling phase in all directions. To describe the distribution of transverse inherent strain through thickness more accurately, a composite shell element is employed, which can divide the thickness into multiple layers and set different material properties. A three-dimensional (3D) thermo–elastic–plastic finite element method (TEP-FEM) model is also developed to simulate the welding process of a thin plate and compute the inherent strain. Moreover, an experiment was performed to verify the accuracy of the numerical model. Comparing the results from experimental data, TEP-FEM, and the proposed method, it is discovered that the new method can predict the deformation of a thin-plate welded joint with good computational accuracy. Highlights: Welded thin metal structures are subjected to thermal deformation by welding process. On the basis of inherent strain theory, an equivalent thermal strain method is proposed to predict welding deformation of thin metal plate. The developed method can predict not only the transverse shrinkage and angular distortion, but also the longitudinal bending deformation accurately. Since the developed method is using an elastic FE analysis, it consumes a dramatically reduced calculation time compared to the thermo-elastic-plastic FE method.